2019
DOI: 10.3390/toxins11080480
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Review of Leydig Cell Lesions in Ochratoxin A-Treated Fischer Rats and Controls

Abstract: Ochratoxin A is best known as a potent renal carcinogen in male rats and mice after necessarily protracted ingestion, although valid extrapolation to any human disease has not been verified. The hypothesis that the toxin is a cause of human testicular cancer was proposed a decade ago and has proliferated since, partly through incomplete study of the scientific literature. Archived tumorous rat testes were available from Fischer F344 rats exposed to continuous dietary exposure for half of or the whole life in L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…There was also insistence that experimental creation of OTA/DNA adducts in testes of newborn mice, from the mother’s intrauterine exposure to a quite large OTA insult (2.5 mg/kg b wt) about 4 days previously, without discounting OTA/DNA adducts in newborn blood. Application of immunohistochemistry to histology review of rat testis tumours has since showed [ 25 ] the distinctive difference between the natural rat Leydig cell tumours and the germinal cell preponderance of human testicular tumours.…”
Section: Discussionmentioning
confidence: 99%
“…There was also insistence that experimental creation of OTA/DNA adducts in testes of newborn mice, from the mother’s intrauterine exposure to a quite large OTA insult (2.5 mg/kg b wt) about 4 days previously, without discounting OTA/DNA adducts in newborn blood. Application of immunohistochemistry to histology review of rat testis tumours has since showed [ 25 ] the distinctive difference between the natural rat Leydig cell tumours and the germinal cell preponderance of human testicular tumours.…”
Section: Discussionmentioning
confidence: 99%
“…From the nearly 60 years of history above it could be expected that most of the renal pelvis tumours sourced for the present study in the context of BEN could be linked aetiologically to that renal disease, but not necessary all. We have recent experience in applying clinical immunohistochemistry (IHC) to review of experimental cancers in rats given protracted or lifetime exposure to ochratoxin A [12,13]. Refinement of histopathology, of value in offering new understanding of the origin and context of cancers, contrasts with literature illustration of BEN-associated tumours [14,15] partly due to risks of postmortem tissue changes in subjects who most likely die at home.…”
Section: Introductionmentioning
confidence: 99%